2013
DOI: 10.1007/s11356-013-2018-x
|View full text |Cite
|
Sign up to set email alerts
|

Dioxin-like activity in sediments from Tai Lake, China determined by use of the H4IIE-luc bioassay and quantification of individual AhR agonists

Abstract: Deterioration of the general ecosystem and specifically quality of the water in Tai Lake (Ch: Taihu), the third largest freshwater in China, is of great concern. However, knowledge on status and trends of dioxin-like compounds in Tai Lake was limited. This study investigated AhR-mediated potency and quantified potential aryl hydrocarbon receptor (AhR) agonists in sediments from four regions (Meiliang Bay, Zhushan Lake, Lake Center, Corner of Zhushan Lake, and Meiliang Bay) of Tai Lake by use of the in vitro H4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
15
2
Order By: Relevance
“…EROD induction potential of the sediment extracts from the Yangtze River estuary was comparable to that of the sediment extracts from River Elbe estuary [41] and Saginaw Bay [42]. The sediment extracts from the Yangtze River estuary showed higher EROD induction potential than those from Masan Bay [43], Tai Lake [44], and Yellow Sea [45]. The EROD induction potential of the sediment extracts from the Yangtze River estuary was also lower than that of the sediments from Tietê River [34], Morava River [14], Dagu Rivers, and Haihe [46].…”
Section: Resultsmentioning
confidence: 66%
“…EROD induction potential of the sediment extracts from the Yangtze River estuary was comparable to that of the sediment extracts from River Elbe estuary [41] and Saginaw Bay [42]. The sediment extracts from the Yangtze River estuary showed higher EROD induction potential than those from Masan Bay [43], Tai Lake [44], and Yellow Sea [45]. The EROD induction potential of the sediment extracts from the Yangtze River estuary was also lower than that of the sediments from Tietê River [34], Morava River [14], Dagu Rivers, and Haihe [46].…”
Section: Resultsmentioning
confidence: 66%
“…6 The bioassay-derived TCDD-EQs were estimated at EC20, EC50 and EC80 to assess whether assumptions of parallel slopes and equal efficacies had been met. 23,28 To minimize biases caused by not meeting the assumption of parallelism, the EC20 was reported.…”
Section: Cell Culture and Bioassaymentioning
confidence: 99%
“…Concentrations of TCDD-EQs were estimated by comparing the dose-response curves of the testing samples and the standards. 23,29 Limits of detection (LOD) based on EC20, EC50 or EC80 were 0.16 AE 0.01 pg per well (4.2 AE 0.9% TCDD-max), 0.58 AE 0.12 pg per well, 2.58 AE 0.49 pg per well and 9.47 AE 1.33 pg per well, respectively.…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the chemical activated luciferase expression (CALUX) assay using mouse hepatoma Hepa1c1c7 cells and the dioxin responsive-CALUX (DR-CALUX) assay using rat hepatoma H4IIE cells are widely used as alternatives to HRGC-HRMS analysis to determine PCDDs and DL-PCBs both rapidly and inexpensively. A number of studies have reported the utility of these reporter gene assay systems as possible alternatives for the screening of dioxins in fish sold for human consumption (Tsutsumi et al 2003), human blood plasma (Croes et al 2011;Van Wouwe et al 2004), bovine milk (Bovee et al 1998), human milk , fly ash (Till et al 1997), and river, lake, and marine sediments (Jung et al 2012;Takigami et al 2005;Vondracek et al 2001;Xia et al 2014). In 2008, we developed a novel sensitive and rapid reporter gene assay (DR-EcoScreen assay) using a genetically engineered stable cell line, designated DR-EcoScreen cells, which can detect 2,3,7,8-TCDD at lower concentrations than other AhR-mediated reporter gene assays (Takeuchi et al 2008;He et al 2011).…”
Section: Introductionmentioning
confidence: 99%